IMPASSES, DESAFIOS E BROTOS: O papel da Assessoria na Transição Agroecológica em Assentamentos Rurais - Araújo, Joaquim Pinheiro de (2009)
This thesis is the result of a study on the role of technical assistance in the process of agroecological transition, which are under way in rural settlements in the territory of Mato Grande, Rio Grande do Norte. Your goal is, from the Technical Assistance Program, Social and Environmental (ATES), launched in 2004 by INCRA understand to what extent this action accomplished their goal of doing a job with a focus on agroecology. To this end, we chose to work with a qualitative methodology, through interviews with settlers, advisors and representatives of INCRA. They also contributed to developing this thesis, the direct observations, which offer visits to settlements and advisory bodies in the Rede Pardal, apart from participation in meetings and activities in which they were being discussed the issues of advice, agroecology and rural settlements. The thesis is divided into five chapters, plus introduction and conclusion. The first three refer to a theoretical analysis and historical about the process of land reform, and as a result the establishment of rural settlements, the importance of peasant tradition for the design of agro-ecological design and the relationship between agricultural models and proposals advice to the countryside. In two subsequent chapters, there was a panoramic picture of the territory of Mato Grande, settlements and groups that make up this research, for then analyze the performance of advisory services in these settlements, with the parameter, agroecology. It was found that the advice in this perspective, suffers a series of constraints, causing a gap between the ideal proposed in the manual and the actual practiced in their daily lives. Still, it is concluded that the ATES has contributed to innovations in productive groups who are experiencing agroecological processes, which can be regarded as shoots for the transition to a new dynamic of development.